Modern Art : Impressionism to Post-Modernism - Ades, Dawn; Britt, David; Denvir, Bernard; Everitt, Anthony; Livingstone, Marco; Mackintosh, Alastair; Nash, J.M.; Wilson, Simon (Boston - Toronto - London : A Bulfinch Press Book Little, Brown and Company Boston, Toronto, London, 1989)
With more than four hundred color illustrations, this concise and authoritative introduction covers every major development in the visual arts in the last one hundred years. Unlike most surveys of this period, Modern Art begins with an in-depth look at Impressionism, before carrying the reader through to the Post-Modernism of the present. Modern Art is an ideal introduction for those new to the field and a highly informed and useful source (complete with chronologies and bibliographies) for the initiated. Anyone seeking a gallery of the masterpieces of twentieth-century art, together with a comprehensive survey of the period, will find no better single volume.
Adami, Valerio ; Albers, Josef ; Alberti, Leon Baptista ; Alechinsky, Pierre ; Alloway, Lawrence ; Andre, Carl ; de Andrea, John ; Apollinaire, Guillaume ; Appel, Karel ; Aragon, Louis ; Archipenko, Aleksandr ; Arikha, Avigdor ; Arman ; Arp, Hans (Jean) ; Art & Language ; Artschwager, Richard ; Atlan, Jean-Michel ; Auerbach, Frank ; Baader, Johannes ; Baargeld, Johannes Theodor ; Bacon, Francis ; Baldung, Hans ; Ball, Hugo ; Balla, Giacomo ; Balthus ; Banham, Reyner ; Barlach, Ernst ; Baron, Jacques ; Baselitz, Georg ; Basquiat, Jean-Michel ; Baudelaire, Charles ; Bazaine, Jean ; Bazile, Frédéric ; Baziotes, William ; Beardsley, Aubrey ; Becher, Johannes ; Bechtle, Robert ; Beckmann, Max ; Beggarstaff Brothers ; Bellmer, Hans ; Bengston, Billy ; Benton, Thomas ; Bergson, Henri ; Bernard, Emile ; Beuys, Joseph ; Blake, Peter ; Bloy, Léon ; Boccioni, Umberto ; Böcklin, Arnold ; Bonnard, Pierre ; Borofsky, Jonathan ; Bosch, Hieronymus ; Boshier, Derek ; Boudin, Eugène ; Boyd, Arthur ; Bradley, William ; Braque, Georges ; Brauner, Victor ; Bresdin, Rodolphe ; Breton, André ; Brisley, Stuart ; Bronson, A.A. ; Broodthaers, Marcel ; Brooks, James ; Brown, Ford Madox ; Bruegel, Pieter ; Brus, Günter ; Buckley, Stephen ; Bunuel, Luis ; Buren, Daniel ; Burgin, Victor ; Burne-Jones, Edward ; Burri, Alberto ; Burton, Scott ; Caillebotte, Gustave ; Caro, Anthony ; Carrà, Carlo ; Cassatt, Mary ; Caulfield, Patrick ; César ; Cézanne, Paul ; Chagall, Marc ; Chamberlain, John ; Chardin, Jean-Baptiste-Siméon ; Chevreul, Eugène ; Chia, Sandro ; Childs, Lucinda ; De Chirico, Giorgio ; Christo ; Clemente, Francesco ; Cohen, Bernard ; Coleridge, Samuel Taylor ; Constable, John ; Constant ; Corinth, Lovis ; Corneille ; Corot, Jean-Baptiste Camille ; Correggio, Antonio Allegri ; etc.
Chronologies and Select Bibliographies p. 406-408
Engels
boek
Keywords: 20ste eeuw